PENGGUNAAN PELACAK NONRADIOAKTIF (Digoxigenin-DNA Probe) UNTUK MENDETEKSI PEANUT STRIPE VIRUS - Hasriadi Mat Akin (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2001)
The use of nonradioactive probe (Digoxigenin-DNA) for detection of peanut stripe virus. The objective of this experiment was to develop the nonradioactive-labeled probe to detect peanut stripe virus (PStV) in peanut leaves and seeds. Digoxigenin labeled cDNA (dig-DNA probe) was synthesized from recombinant plasmid (pHS1.23) using polymerase chain reaction (PCR). The probe containing 1.195 bp (base pair) corresponding to 3' termini, included part of NIb (nuclear inclusion body) gene, coat protein gene, and 3' untranslated region of PStV genome was used to detect the existence of PStV in peanut leaves and seeds of infected peanut plants.